2003
DOI: 10.1016/s0092-8674(03)00043-6
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe Int6 and Ras Homologs Regulate Cell Division and Mitotic Fidelity via the Proteasome

Abstract: Yin6 is a yeast homolog of Int6, which is implicated in tumorigenesis. We show that Yin6 binds to and regulates proteasome activity. Overexpression of Yin6 strengthens proteasome function while inactivation weakens and causes the accumulation of polyubiquitinated proteins including securin/Cut2 and cyclin/Cdc13. Yin6 regulates the proteasome by preferentially interacting with Rpn5, a conserved proteasome subunit, and affecting its localization/assembly. We showed previously that Yin6 cooperates with Ras1 to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 61 publications
(3 reference statements)
4
111
1
2
Order By: Relevance
“…In fission yeast, it was proposed that SpRpn5, together with the human breast cancer related gene Int6/Yin6, serves for the nuclear localization of the lid (Yen et al, 2003b), although our results showed that the lid rpn7-3 containing Rpn5p was not localized in the nucleus (Figure 7, A and B). One explanation of these seemingly controversial results may be that there is no Int6/Yin6 homologue in budding yeast and hence the Int6/Yin6 associated function of Rpn5p is not conserved in the two yeast species.…”
Section: Discussioncontrasting
confidence: 60%
“…In fission yeast, it was proposed that SpRpn5, together with the human breast cancer related gene Int6/Yin6, serves for the nuclear localization of the lid (Yen et al, 2003b), although our results showed that the lid rpn7-3 containing Rpn5p was not localized in the nucleus (Figure 7, A and B). One explanation of these seemingly controversial results may be that there is no Int6/Yin6 homologue in budding yeast and hence the Int6/Yin6 associated function of Rpn5p is not conserved in the two yeast species.…”
Section: Discussioncontrasting
confidence: 60%
“…In addition, eIF3e has been reported to interact with subunits of the proteasome and the COP9 signalosome, suggesting its possible involvement in the regulation of both protein synthesis and degradation (von Arnim and Chamovitz, 2003). Inactivation of fission yeast eIF3e compromised proteasome function and caused the accumulation of polyubiquitinylated proteins (Yen et al, 2003). In Drosophila eIF3e was shown to be a positive regulator of cullin neddylation, thus regulating degradation through the ubiquitin-proteasome pathway of substrates of cullin-containing ubiquitin ligases (RencusLazar et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…eIF3e regulates a specific subset of mRNAs Previous reports have concluded that, besides binding other components of eIF3, eIF3e can associate separately with subunits of the proteasome (Asano et al, 1997;Yen et al, 2003;Zhou et al, 2005). We therefore further investigated the potential involvement of eIF3e in regulation of global protein levels through translation initiation and/or proteolysis through the ubiquitinproteasome pathway.…”
Section: Elevated Eif3e Protein Levels In Human Breast Cancermentioning
confidence: 99%
“…In yeast, Yen et al (2003) have shown that Int-6 binds Rpn5 and mediates its nuclear import. In the absence of this event, the proteasome assembly is affected, thus resulting in a general protein degradation defect that impairs the metaphase-anaphase transition.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Yen et al have shown that combination of Int-6 depletion with proteasome subunit mutants leads to a blockade of fission yeast division at the metaphase to anaphase transition. This results from a defect of cyclin B1 and securin degradation, which correlates with impairment of Rpn5 transport into the nucleus ending in proteasome malfunction (Yen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%